EKSPLORASI JENIS DAN PEMANFAATAN TANAMAN ENDEMIK DAN LOKAL DI KECAMATAN BOGOR SELATAN - Shafa Noer; Mashudi Alamsyah; Rina Hidayati Pratiwi; Maya Fadhillah (Jurnal Biogenerasi, 2026)
South Bogor District is an area with agroecosystem conditions that still support the existence of endemic and local plant species utilized by local communities. However, scientific information regarding species diversity, utilization patterns, and sustainability potential remains limited. This study aimed to explore the diversity of endemic plants, their utilization forms, plant parts used, as well as community perceptions and threats to their existence in South Bogor District. The research employed a descriptive survey method with an ethnobotanical approach through field observations and semi-structured interviews with local residents. The results revealed various endemic and local plant species utilized by the community, predominantly for medicinal purposes, food, and spices. The most frequently used plant parts were fruits, leaves, and rhizomes, with processing methods that remain simple and based on traditional knowledge. Community perception toward the importance of endemic plants was highly positive; however, high utilization intensity of certain species was not always aligned with their availability in nature. Major threats to the sustainability of endemic plants include land-use change, logging, inadequate plant maintenance, and limited replanting efforts. This study highlights that endemic plants in South Bogor District play essential ecological, social, and cultural roles, yet require community-based management and conservation strategies to ensure their sustainable utilization.